2023
DOI: 10.1371/journal.pone.0264802
|View full text |Cite
|
Sign up to set email alerts
|

Fructose-containing food sources and blood pressure: A systematic review and meta-analysis of controlled feeding trials

Abstract: Whether food source or energy mediates the effect of fructose-containing sugars on blood pressure (BP) is unclear. We conducted a systematic review and meta-analysis of the effect of different food sources of fructose-containing sugars at different levels of energy control on BP. We searched MEDLINE, Embase and the Cochrane Library through June 2021 for controlled trials ≥7-days. We prespecified 4 trial designs: substitution (energy matched substitution of sugars); addition (excess energy from sugars added); s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 181 publications
1
1
0
Order By: Relevance
“…The lack of change in central hemodynamics could be attributed to the intervention's short duration [46]. Nonetheless, the reduction in peripheral blood pressure was consistent with previous findings on the cardiovascular benefits of fruit juice consumption [47,48], particularly in lowering systolic BP [49][50][51]. Our results are in partial agreement with a meta-analysis reporting that probiotic consumption significantly decreased systolic BP by −3.56 mmHg and diastolic BP by −2.38 mmHg compared to those in control groups, with a greater reduction in BP found with multiple probiotics compared to single probiotics, as well as greater reductions being found in diastolic BP in hypertensive patients [52].…”
Section: Discussionsupporting
confidence: 87%
“…The lack of change in central hemodynamics could be attributed to the intervention's short duration [46]. Nonetheless, the reduction in peripheral blood pressure was consistent with previous findings on the cardiovascular benefits of fruit juice consumption [47,48], particularly in lowering systolic BP [49][50][51]. Our results are in partial agreement with a meta-analysis reporting that probiotic consumption significantly decreased systolic BP by −3.56 mmHg and diastolic BP by −2.38 mmHg compared to those in control groups, with a greater reduction in BP found with multiple probiotics compared to single probiotics, as well as greater reductions being found in diastolic BP in hypertensive patients [52].…”
Section: Discussionsupporting
confidence: 87%
“…A recent meta-analysis of clinical trials shows small doses of 100% fruit juice are beneficial in minimizing hypertension though the effect was minimal but crucial. However, mixing fruit juice with sugar-sweetened beverages (up to ∼23%) moderately increases blood pressure while removal of sugar-sweetened beverages decreases blood pressure irrespective of the presence or absence of hypertension (Liu et al, 2023). Consistently, another observational study from West African countries reported that higher consumption of red meat, dietary fat, salt, junk food, and alcohol are linked with increased blood pressure and hypertension while higher consumption of fruit and vegetables was protective against hypertension (Batubo et al, 2023).…”
mentioning
confidence: 99%